Impacts of COVID-19 on Firms in Malaysia : Results from the 3rd Round of COVID-19 Business Pulse Survey - Kuriakose, Smita; Tran, Trang; Ting, Kok Onn; Hebous, Sarah (World Bank, Washington, DC, 2021)
The COVID-19 Business Pulse Survey (BPS) is a rapid survey designed to measure the various channels of impact of COVID-19 on firms, firm adjustment strategies, and public policy responses. The World Bank, in collaboration with a private survey company, conducted the 3rd round of survey in July 2021, following the 1st round in October 2020 and 2nd round of the Malaysia BPS in Mid-January to February 2021. Firms were sampled randomly from an online business panel database, which consists of 100,000+ companies in all sectors and sizes, across Peninsular and East Malaysia. A minimum sample size was obtained for sectors that are important to Malaysia’s economy and are sensitive to the COVID-19 crisis (export-oriented activities: electronics, automotive, tourism related activities) while preserving the sectoral shares in the sampling frame. The survey was conducted online and yielded 1,500 responses from respondents in senior management positions at their company (i.e. owners, C-suite or Director level).